Diethyl Phosphite Promoted Electrochemical Oxidation of Tetrahydroisoquinolines to 3,4-Dihydroisoquinolin-1(2H)-ones - Xie, Wenxia; Gong, Bowen; Ning, Shulin; Liu, Nian; Zhang, Zhuoqi; Che, Xin; Zheng, Lianyou; Xiang, Jinbao (Synlett, 2019)
A diethyl phosphite mediated electrochemical oxidation strategy for the synthesis of 3,4-dihydroisoquinolin-1(2H)-ones from tetrahydroisoquinolines under mild conditions has been developed. This protocol provides an environmentally friendly and simple way for the construction of C=O bonds in an undivided cell unit.
Keywords: electrochemistry; oxidation; diethyl phosphite; tetrahydroisoquinoline; C=O bond formation